Implementasi Keberlanjutan Pengelolaan Dana Zakat Untuk Meningkatkan Kesejahteraan Masyarakat : Studi Kasus di LKS Al-Yasini Pusat - M. Badrus Sholeh; Diana, Ilfi Nur; Rofiq, Aunur (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
This study aims to describe the implementation of sustainable zakat fund management in improving community welfare at LKS Al-Yasini. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. Data were analyzed with the steps of data processing, data classification, data interpretation, and drawing conclusions. The results of the study indicate that the implementation of sustainable zakat fund management at LKS Al-Yasini has provided real benefits for the welfare of the local community. However, there are still several obstacles faced in the implementation of this program. Therefore, it is recommended that LKS Al-Yasini continue to evaluate and improve the management of zakat funds in order to increase the effectiveness of the program.